Monetary Model of Ringgit Exchange - H. Abas, Khairizah; Yusof, Z.; Samsi, Siti Muliana (2010)
This study re-examines the dynamic linkages between exchange rate and its monetary fundamentals namely, money, income and interest rate in a small emerging state of Malaysia. It investigates the short-run dynamics and long run relationships between ringgit exchange and its fundamental monetary variables. Based on the flexible price monetary framework, the model was tested via Johansen cointegration technique and vector error correction model using data set from 1980:Q1 to 2008:Q3. The findings suggest a strong evidence of long run relationship between exchange rate and the monetary fundamentals in Malaysia. Interestingly, further examination demonstrates that ringgit adjusts gradually to changes in money, income and interest rate, generally implying less volatile ringgit.